South-Polish palinocomplex as longlasting record of different scale climatic changes at the early Pleistocene transition (MIS 22–13): https://doi.org/10.26485/AGL/2017/106/11 - Winter, Hanna (Acta Geographica Lodziensia, 2018)
The South-Polish pollen complex, being an equivalent of the South-Polish complex in relation to its pollen content, was distinguished based on pollen data coupled with palaeomagnetic and geological investigations. The complex contains the Augustovian, Domuratovian and Ferdynandovian pollen sequences with a multicycle record of vegetation changes. The record of vegetation changes allows for the reconstruction of high-amplitude climate changes of a glacial/cooling/glacial rank and low-amplitude changes such as interstadial/stadial oscillations and climate fluctuations taking place both during interglacials and cool intervals. Based on palaeomagnetic data, vegetation and climate changes, the Augustovian succession should be correlated with MIS 21–19, the Domuratovian succession – with MIS 17, and the Ferdynandovian succession – with MIS 15–13.